Can granulomatosis with polyangiitis be diagnosed earlier in primary care? A case-control study - Pearce, Fiona A.; Hubbard, Richard; Grainge, Matthew J.; Watts, Richard A.; Abhishek, Abhishek; Lanyon, Peter C. (Oxford University Press, 2017)
Background: People with granulomatosis with polyangiitis (GPA) commonly describe long delays before diagnosis. Aim: To study the natural history of GPA prior to diagnosis using primary care data, and determine whether clinical features could be identified to help earlier diagnosis.DesignCase-control study using the Clinical Practice Research Datalink. Methods: We compared primary care activity and clinical features between cases and 10 matched controls. Results: We identified 757 cases and matched 7,546 controls. Compared to controls, cases had more GP consultations and overall healthcare activity in the five years prior to their diagnosis, with a marked increase in the year before diagnosis, and particularly in the last 3 months. However, consultations were mostly for symptoms that were not specifically related to GPA. In the year prior to diagnosis, the most frequent and strongly predictive clinical features of GPA were Ear Nose and Throat (ENT) symptoms (34.5% of cases, odds ratio (OR) 10.5, 95% confidence intervals (CI) 8.6-12.7), and general (constitutional) symptoms (21.5% of cases, OR 9.0, 95% CI 7.1-11.3). In the year before diagnosis a larger number of cases attended secondary care (382, 50.5%) than had records of clinical features of GPA. Conclusions: After discussing our findings, we conclude it would be difficult to identify cases of GPA earlier in primary care. Our results support a need for heightened awareness of this condition among secondary care clinicians, especially those assessing emergency admissions, and in the clinics which were most frequently attended by cases 3-12 months prior to diagnosis.